2011
DOI: 10.1007/s13191-011-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional Status and Eating Pattern in First and Second-Time Denture Wearers: A Prospective 60 Days (2 Months) Pilot Study

Abstract: Elderly individuals with extensive tooth loss preferentially consume soft, easier to chew foods which have a low nutrient density. The purpose of this study was to suggest that every complete denture wearer has to be periodically counseled by a registered Dietician and Dentist for check up to avoid malnutrition and disease. Fourteen patients were selected for this study. Seven of them with four or five teeth remaining without any functional units and seven patients who were known cases of complete denture wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
9
2
Order By: Relevance
“…[ 9 ] Further, the consequences of compromised dental function can be swallowing of poorly chewed food, food avoidance patterns, dietary inadequacies, reduced vigor, debilitation, and shortened life expectancy. [ 10 ] The subjective evaluation of oral health-related quality of life (OHRQoL) “reflects people's comfort when eating, sleeping, and engaging in social interaction; their self-esteem; and their satisfaction with respect to their oral health.”[ 11 ] The Oral Health Impact Profile (OHIP) was developed by Slade and Spencer[ 12 ] as one of the tools for evaluating OHRQoL, which was later modified as the shortened version of the OHIP and validated (OHIP-14). [ 13 ] The chewing problems lead to diminished perceived oral health, which in turn results in treatment demand in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Further, the consequences of compromised dental function can be swallowing of poorly chewed food, food avoidance patterns, dietary inadequacies, reduced vigor, debilitation, and shortened life expectancy. [ 10 ] The subjective evaluation of oral health-related quality of life (OHRQoL) “reflects people's comfort when eating, sleeping, and engaging in social interaction; their self-esteem; and their satisfaction with respect to their oral health.”[ 11 ] The Oral Health Impact Profile (OHIP) was developed by Slade and Spencer[ 12 ] as one of the tools for evaluating OHRQoL, which was later modified as the shortened version of the OHIP and validated (OHIP-14). [ 13 ] The chewing problems lead to diminished perceived oral health, which in turn results in treatment demand in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were found in the study by Dable et al 9 and Norlela et al 14 The lowest mean GOHAI score contributes a significant burden on the individual and the community. Masticatory ability and food selection are largely affected by loss of teeth forcing edentulous people to choose soft and easy to chew food compared to dentate individuals 16,17 and they therefore constitute the group most likely to change their diet. 18 The highest mean GOHAI score was found to be able to swallow comfortably and similar result was found in study by Shigli et al 10 In contrast to the findings in the study by Dable et al, 9 in the present study, there was lesser degree of impairment in speaking and swallowing due to loss of teeth.…”
Section: Resultsmentioning
confidence: 99%
“…Higher chewing ability in patients with MICD compared to the group without MICD is the reason of lower changes in food intake. In connection with this, recent studies showed statistically significant increase in nutrition during the study period after insertion of complete denture and associations between changes in dental status and dietary intake of specific nutrients [8,9,10]. Madhuri et al [16] reported an increase of consumption of protein, fruits and vegetables in denture wearers after insertion of complete dentures in comparison to the period when patients were edentate.…”
Section: Discussionmentioning
confidence: 95%
“…Besides relationship between metabolic control of DM and oral health status [6], studies have also shown higher prevalence of missing teeth and teeth with deep pockets indicated for extractions in diabetic patients compared to nondiabetics [7]. Alterations in oral status and loss of teeth affect masticatory ability and food selection [8,9,10]. In connection with this, complete and partially edentulous patients showed nutrition disadvantage with reduced intake of dietary fiber and vitamins B6, C, carbohydrates, beta-carotene, and folate [11,12].…”
Section: Introductionmentioning
confidence: 99%